Radiological risks assessment of building materials ingredients: Palm oil clinker and fuel ash - Karim, Mohammad Razaul; Khandaker, Mayeen Uddin; Asaduzzaman, Khandoker; Razak, Hashim Abdul; Yusoff, Sumiani (SAGE Publications, 2019)
Technical benefits relevant to the use of palm oil clinker (POC) and fuel ash (POFA) in building materials has been well documented. However, the radiological health hazards caused by the incorporation of POC and POFA as an ingredient of building materials have not been studied so far. The radioactivity levels were measured by γ-ray spectrometry using hyper-pure germanium (HPGe) detector. The activity concentration of 226 Ra and 232 Th in POC and POFA was found to be in the ranges of 5.56 ± 0.23 to 9.03 ± 0.21 and 4.21 ± 0.03 to 7.98 ± 0.19 Bq kg −1 , respectively, and these values were lower than the world average values of 50 Bq kg −1 for building materials. The 40 K value was within the range of 413.01 ± 1.78 to 604.66 ± 2.18 Bq kg −1 . Several radiological parameters and hazard indices, i.e. radium equivalent activity, absorbed dose rate and annual effective dose etc. were calculated for the evaluation of the potential radiological hazards. The obtained values fall within the recommended limit set by various international organizations. Since the activity levels of 226 Ra, 232 Th and 40 K in POC and POFA were significantly lower than the corresponding literature data for other ingredients of building materials, it indicates that POC and POFA are safe to be used in concrete construction. © The Author(s) 2018.